Histopathology of Failed Descemet Membrane Endothelial Transfer. (September 2018) - Parker, Jack; Verdijk, Robert M.; Müller, Thomas M.; Lavy, Itay; Bruinsma, Marieke; Colby, Kathryn; Binder, Perry S.; Melles, Gerrit R. J.
Abstract : Objectives: To describe the postmortem histologic features after an unsuccessful Descemet membrane endothelial transfer (DMET) and assess any potential clinical implications. Methods: Postmortem, an eye from a patient who previously underwent unsuccessful DMET for pseudophakic bullous keratopathy (PPBK) was harvested and processed for morphologic evaluation. Results: Clinically and histologically, the host cornea showed evidence of diffuse stromal edema. Although the edges of the surgical descemetorhexis were well visualized, there was no evidence of endothelial migration or repopulation of the posterior stroma from any direction. A multilayered, retrocorneal membrane was present that appeared to originate from the trabecular meshwork. Conclusions: Descemet membrane endothelial transfer and "descemetorhexis alone" may be insufficient treatment for eyes operated on for PPBK, that is, eyes with a significantly depleted or dysfunctional endothelium.